2017
DOI: 10.4236/ojg.2017.71007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Post Orogenic A-Type Granite, Gabal El Atawi, Central Eastern Desert, Egypt: Geochemical and Radioactive Perspectives

Abstract: The alkali feldspar granite of Gabal El Atawi is post orogenic granite originated from subalkaline magma in extensional suite. It is developed within plate tectonic setting and has A 2 -type character which generated from apparent crustal source. The petrographic, geochemical and radioactive characteristics of El Atawi granite meet and fulfill the requirements of being fertile granite and it can be considered as promising uraniferous granite. Fluid inclusion studies of the altered granite elucidated two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This may apply to fluorites of El-Missikat area. There is close similarity in REY pattern of the present fluorites and Sardinian fluorites, Italy (group A) (Castorina et al 2008) and other fluorite areas in the Eastern Desert of Egypt (Mahdy et al 2013 andFawzy, 2017). Fleischer (1969) showed that the fluorites from a single location may exhibit different REE abundances, controlled by the variability of the parameters governing the mineralizing process.…”
Section: Genesis Of Fluorite Mineralizationmentioning
confidence: 56%
See 1 more Smart Citation
“…This may apply to fluorites of El-Missikat area. There is close similarity in REY pattern of the present fluorites and Sardinian fluorites, Italy (group A) (Castorina et al 2008) and other fluorite areas in the Eastern Desert of Egypt (Mahdy et al 2013 andFawzy, 2017). Fleischer (1969) showed that the fluorites from a single location may exhibit different REE abundances, controlled by the variability of the parameters governing the mineralizing process.…”
Section: Genesis Of Fluorite Mineralizationmentioning
confidence: 56%
“…Numerous geological and geochemical data on the fluorite veins in the Eastern Desert were carred out (e.g. Yonan,1990;El-Mansi, 1993;Mohamed and Bishara, 1998;Fawzy et al,1996;Fawzy, 2001;Salem et al, 2001;Ali, 2001;Yonan and El-Kammar, 2001;Mohamed, 2013;Mahdy et al, 2013, El Hadek et al, 2016and Fawzy, 2017.…”
Section: Introductionmentioning
confidence: 99%